Evaluation of autologous skeletal muscle-derived factors for regenerative medicine applications. Issue 5 (May 2017) - Yoshikawa, M.; Nakasa, T.; Ishikawa, M.; Adachi, N.; Ochi, M.
Abstract : Objectives: Regenerative medicine is an emerging field aimed at the repair and regeneration of various tissues. To this end, cytokines (CKs), growth factors (GFs), and stem/progenitor cells have been applied in this field. However, obtaining and preparing these candidates requires invasive, costly, and time-consuming procedures. We hypothesised that skeletal muscle could be a favorable candidate tissue for the concept of a point-of-care approach. The purpose of this study was to characterize and confirm the biological potential of skeletal muscle supernatant for use in regenerative medicine. Methods: Semitendinosus muscle was used after harvesting tendon from patients who underwent anterior cruciate ligament reconstructions. A total of 500 milligrams of stripped muscle was minced and mixed with 1 mL of saline. The collected supernatant was analysed by enzyme-linked immunosorbent assay (ELISA) and flow cytometry. The biological effects of the supernatant on cell proliferation, osteogenesis, and angiogenesis in vitro were evaluated using human mesenchymal stem cells (hMSCs) and human umbilical cord vein endothelial cells (HUVECs). Results: The supernatant contained several GFs/CKs, with especially high levels of basic fibroblast growth factor, and CD34+ cells as the stem/progenitor cell fraction. With regard to biological potential, we confirmed that cell proliferation, osteoinduction, and angiogenesis in hMSCs and HUVECs were enhanced by the supernatant. Conclusions: The current study demonstrates the potential of a new point-of-care strategy for regenerative medicine using skeletal muscle supernatant. This attractive approach and readily-available material could be a promising option for tissue repair/regeneration in the clinical setting. Cite this article : M. Yoshikawa, T. Nakasa, M. Ishikawa, N. Adachi, M. Ochi. Evaluation of autologous skeletal muscle-derived factors for regenerative medicine applications. Bone Joint Res 2017;6:277–283. DOI: 10.1302/2046-3758.65.BJR-2016-0187.R1.